Tracing Knowledge Flow as Strategy towards Measuring Corporate Knowledge - Syed Mustapha, S.M.F.D (International Journal of Advanced Corporate Learning (iJAC), 2017)
Corporate knowledge is essential mainly to knowledge-intensive organizations. Its success is always associated with the performance of the organization through ROI (Return of Investment). While the scope of corporate knowledge is wide, we redefine in the context of computational environment and demonstrate how corporate knowledge can be modelled and subsequently enabled it to be measured. With this new ability, the knowledge flow within the learning activities can be traced and the individual performance can be measured based on the learning goal being set.